In Vitro Biocontrol of Escherichia coli Through the Immobilization of its Specific Lytic Bacteriophage on Cellulose Acetate Biodegradable Film - Samaneh Faraji Kafshgari; Yahya Maghsoudlou; Morteza Khomeyri; Mahboubeh Kashiri; Arash Babaei (Iranian Journal of Medical Microbiology, 2019)
Background and Aims: Bacteriophages are mandatory bacterial parasites that are harmless to human and animal, which are used by dipping or spraying in food as natural antimicrobial agents. The use of these methods leads to wasting or trapping of phage in food, but its immobilization on the polymer surface facilitates the contact of phage with the host cell at the food surface. Therefore, the aim of this study was to immobilize the lytic phage of Escherichia coli on the cellulose acetate film and investigate of its antimicrobial effect. Materials and Methods: Escherichia.coli bacteria was incubated at 37°C for 24 hours, and the antimicrobial effect of phages was evaluated through plaque forming. The cellulose acetate film was prepared by casting, then modificated by plasma, and immersed in a suspension of phage (1010 PFU/ml) and incubated at 37 °C for 24 hours with slow shaking, then the number of immobilized phages was estimated. To confirm the immobilization, FESEM was done. The antimicrobial effect of the active film was evaluated by disk diffusion and the release rate and antimicrobial activity of immobilized phages were investigated in 14 days. Results: Phages formed clear plaques against E.coli. Modification of film by plasma resulted in uniform immobilization (108 PFU/ml) that FESEM revealed it. The active film (with zone diameter 12 mm) showed stronger antimicrobial effect than the antibiotic ampicillin (positive control sample with zone diameter 8 mm). 11 days after the immobilization, the number of immobilized phages decreased from 108 to 106 (PFU/ml) and released from the film surface, afterwards did not release. The antimicrobial activity of active film was decreased due to the absence of host bacteria continuously in 15 days, so that the host bacteria population increased from 3 to 5.3 LOG CFU/ml. Conclusions: In spite of reducing the antimicrobial activity of cellulose acetate active film over the time, due to the presence of host bacteria at food surface and its high potential in destroying the host bacteria, it can be used to increase of food safety in food packaging.